Математичне та програмне забезпечення системи виявлення зворотного гортанного нерва - Падлецька, Наталія Ігорівна (Тернопільський національний економічний університет, 2016)
У дисертації вирішено важливу науково-технічну задачу розроблення математичного та програмного забезпечення прикладної програмної системи виявлення зворотного гортанного нерва з-поміж м’язових тканин на хірургічній рані під час операції на щитоподібній залозі, архітектура та модулі якої відрізняється від інших систем інтегрованим використанням модулів читання, сегментації, виявлення інформативних ознак сигналу – реакції на подразнення зворотного гортанного нерва та модуля прийняття рішень, реалізованих в різних програмних середовищах, яке у сукупності забезпечує використання прикладної програмної системи в режимі реального часу. Удосконалено інформаційну технологію, яка, на відміну від існуючих, забезпечує безпомилкове виявлення зворотного гортанного нерва. В диссертации решена важная научно-техническая задача разработки математического и программного обеспечения прикладной программной системы обнаружения возвратного гортанного нерва среди мышечных тканей на хирургической ране во время операции на щитовидной железе, архитектура и модули которой отличается от других систем интегрированным использованием модулей чтения, сегментации, выявление информативных признаков сигнала – реакции на раздражение возвратного гортанного нерва и модуля принятия решений, реализованных в различных программных средах, которое в совокупности обеспечивает использование прикладной программной системы режиме реального времени. Усовершенствована информационная технология, которая, в отличие от существующих, обеспечивает безошибочное обнаружения возвратного гортанного нерва. In the thesis it was solved the actual scientific and technical task of creation the mathematical methods and software that provides high-performance monitoring the wound on the thyroid gland in real time and correct determining the recurrent laryngeal nerve (RLN). In the first chapter it was analyzed the technical and mathematical tools and software for RLN identification. The analysis revealed the lack of mathematical tools and software with architecture which in the aggregate provides the operation of heterogeneous modules as a unified system aimed at high-performance monitoring the surgery wound and accurately determine RLN placement in real time. In the second chapter it was analyzed the known mathematical models and was received the new models of characteristics of surgery environments as interval estimations of signal energy that is response to stimulation the tissues of surgical wound in the given range of frequencies that increase the reliability of RLN detection during the surgery and reduce the risk of its injury. It was confirmed that the risk of RLN damage reduced in a sample of about 500 patients using the proposed model of characteristics the surgery environment. In the third chapter these were developed a new architecture and modules of applied software system for RLN monitoring which differs from other systems by using the modules of reading, segmentation and identification the informative characteristics of signal as response to RLN stimulation and decisions support module which are realized in various software environments that in general provides the software application using in real time. In the fourth chapter based on the developed mathematical methods and software for RLN detection it was improved the information technology for RLN detection which is, unlike the existing ones, based on mathematical models of informative characteristics and interval analysis the energy spectrum of information signal, provides unmistakable RLN detection during surgery on the thyroid gland in real time. The reliability of obtained theoretical results is confirmed by approval of the developed applied system for RLN detection during surgeries on the thyroid gland for about 500 patients by conductive the comparative analysis of using the information technology in the case of application of known ones and proposed mathematical model of characteristics of the surgery environment in the form of interval estimations the signal energy as reaction to stimulation the tissues in surgical wounds.
Математическое и программное обеспечение системы обнаружения возвратного гортанного нерва
Mathematical methods and software of computer system for detection the recurrent laryngeal nerve
Keywords: інформаційна технологія; математичне та програмне забезпечення; архітектура прикладної програмної системи; зворотний гортанний нерв; щитоподібна залоза; хірургічна рана; м’язова тканина; информационная технология; математическое и программное обеспечение; архитектура прикладной программной системы; возвратный гортанный нерв; щитовидная железа; операционная рана; мышечная ткань; information technology; mathematical methods and software; architecture of application systems; recurrent laryngeal nerve; thyroid; surgical wound; muscle tissue